Hubungan Kadar Merkuri (Hg) dengan Profil Darah Pekerja Pertambangan Emas Tradisional di Desa Jendi Kecamatan Selogiri Kabupaten Wonogiri - Lenci Aryani; Onny Setiani; Nurjazuli Nurjazuli (Master Program of Environmental Health, Faculty of Public Health, Diponegoro University, 2013)
Background: mercury is neurotoxic substance which can produce some health effect, depends on impact ofduration of exposure and quantity mercury used. Gold miner had a high risk of continously impact which maycause many health disorder, one of them is blood profile interference.The purpose of this reasearch was to know the relationship between mercury concentration in blood with bloodprofile of traditional mining gold worker in Jendi village, Selogiri Sub District, Wonogiri District.Methods: The study design was an analytic observational research. Research subject were whole of workers whowere working in mining gold. Variables in this research were mercury (Hg) in blood and blood profile. Datacollection using interview, observation, and measurement technique. Data would be analyzed using Kendal’s Taucorrelation.Result: The results showed that the average of Hg in blood was 7,819 ppb. It was over toxic level (eˆ 5,8 ppb) andaverage blood profile consist of haemoglobin, erythrocyte, leukocyte, platelet, hematocrit, MCV, MCH, andMCHC were 14,771 gr/dl; 4,9536 jt/mmk; 7,5679 rb/mmk; 334,26 rb/mmk; 43,833%, 88,6333 fl; 29,8833 pg;33,6976. Bivariate analysis showed the significant relationship between mercury (Hg) in blood with bloodprofile (amount of leukocyte) p-value 0,017 and rho 0,257.Conclusion: The conclusion of the research was Hg rates in blood had a toxic limit standard so it can change theblood profile (decreased amount of leukocyte). It was recommended for gold miner to used a personal protectiveequipment like mask, lowering smoking habbit, checked-up, and make lots of green area at mining gold.Keywords : mercury in blood, blood profile, mining gold worker